PENGARUH PEMENUHAN KONTRAK PSIKOLOGIS DAN DUKUNGAN ORGANISASI TERHADAP KEPUASAN KARIR YANG DIMEDIASI OLEH PERKEMBANGAN DI TEMPAT KERJA PADA PERAWAT DI RUMAH SAKIT PERTAMEDIKA UMMI ROSNATI KOTA BANDA ACEH - Annisa Ulhusna; Nur Chalil (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to determine the relationship between psychological contract fulfillment and organizational support on career satisfaction with thriving at work as the mediator. Data was obtained through a survey of 122 nurses at Pertamedika Ummi Rosnati Hospital, Banda Aceh City. The data analysis method used is Statistical Product and Service Solutions (SPSS). The results of the study found that psychological contract fulfillment, organizational support and thriving at work directly affect career satisfaction. The results also found that the fulfillment of psychological contracts affects the mediator variable, namely thriving at work, so that thriving at work is able to become a mediator on the influence of the variables of psychological contract fulfillment and organizational support on career satisfaction.This study aims to determine the relationship between psychological contract fulfillment and organizational support on career satisfaction with thriving at work as the mediator. Data was obtained through a survey of 122 nurses at Pertamedika Ummi Rosnati Hospital, Banda Aceh City. The data analysis method used is Statistical Product and Service Solutions (SPSS). The results of the study found that psychological contract fulfillment, organizational support and thriving at work directly affect career satisfaction. The results also found that the fulfillment of psychological contracts affects the mediator variable, namely thriving at work, so that thriving at work is able to become a mediator on the influence of the variables of psychological contract fulfillment and organizational support on career satisfaction.